If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m+(-11/6)=-2/9
We move all terms to the left:
m+(-11/6)-(-2/9)=0
We get rid of parentheses
m-11/6+2/9=0
We calculate fractions
There is no solution for this equation
| -6-74=-9b-7b | | 6d+8+3d+1=180 | | 6a=3(a+4)-a) | | -8-(-3b-6)=28 | | 4v-2+2v-4=90 | | 10-6x=6-5x | | 42+7p=-4p+-2 | | 4v-2+2v-4=180 | | -13x+12=10 | | 1/2(8x+26)=7x-2(4x+13) | | p(3p+29)=84 | | 2y+1+29=180 | | 8x+2+34=90 | | 18=-4m | | 8y-2+60=90 | | (2x+10)x3=180 | | 8y-2+60=180 | | -6x+7=-8x–13 | | 6x+4+5x-2=180 | | 120+y+16=180 | | 5y-7+57=90 | | F(x)=12x-3-7 | | 18=5x-23 | | 5y-7+57=180 | | 6(2x+5=90 | | 2a+3=8a+9 | | w+1+91=90 | | 43m=104+30m | | (3x)/3x+1+(2)/x=1 | | 4w+5+33=180 | | 4w+5+3=90 | | 8/4=w-2/6 |